Determination of anti-HCV signal to cut-off value in patients with hepatitis C virus infection and the variety of antibody responses - Ocal, Murat; Bulut, Mehmet Emin (The European Research Journal, 2023)
Objectives: The diagnosis of hepatitis C virus (HCV) infection starts with the detection of antibodies against recombinant or synthetic HCV proteins by Enzyme Immunoassay (EIA). Although EIA tests are highly sensitive, false positivity rates are not low. Positive anti-HCV results are generally confirmed with complementary tests such as Nucleic Acid Amplification Tests (NAAT), or Western Blot modifications. Methods: The anti-HCV results of 199,516 individuals referred from various clinics between 2015 and 2019 were evaluated retrospectively at University of Health Sciences, Şişli Hamidiye Etfal Training and Research Hospital, Medical Microbiology Laboratory. From the 2039 samples, of which EIA tests resulted borderline and reactive, 1419 samples having Line Immunoassay (LIA) confirmatory test results were included in the study. Results: LIA tests yielded positive, negative and indeterminate for 820 (57.8%), 519 (36.6%) and 80 (5.6%) of 1419 samples, respectively. The optimal threshold point for EIA anti-HCV signal to cut-off (S/Co) according to LIA was found to be 15.85 corresponded to diagnostic sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of 94.9%, 94.8%, 96.6%, 92.1%, 94.9%, respectively. The most common proteins detected in LIA positive samples were C1 96.3%, C2 90.4%, and NS3 93.2%. Conclusions: To prevent false positivities, confirmatory tests must be used for samples with low S/Co ratios. The use of S/Co value will make significant contribution to reducing both false-positive results and the LIA confirmatory test consumption. There was no correlation between the number of bands and EIA index values in LIA positive samples, while the relationship between the number of 3+ bands and index values was remarkable.